(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, the dynamics of stem growth of 15 different varieties of “AVMU” and “Zilola” and “Marjona” varieties at different vegetation periods (three-leaf stage, budding, flowering, ripening) of various mung bean varieties were studied. As a result, it was found that the most positive result was observed in variant 16 and variant 11 among 15 different varieties of “AVMU” according to the experimental system.